2007
DOI: 10.1093/heapro/dal060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of condom use among Bolivian truck drivers through the lens of social cognitive theory

Abstract: SUMMARYThis study demonstrates that Bolivian long distance truck drivers are a high risk population of HIV infection and transmission, supporting other global studies involving truck drivers and their high risk. The aims of this investigation were to estimate the prevalence of high risk behaviors and to identify predictors of condom use in this population.Analysis was completed on survey results from 246 male truckers (aged 18-67). About one in three of the truck drivers (30%) reported having had a sexually tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Long distance truck drivers and their helpers (hereafter referred to as truckers) are considered to be at high risk for sexually transmitted infections (STI) and HIV in many parts of the world, including Asia [14], Africa [58], South America [9, 10] and the United States [11, 12]. Truckers’ increased HIV risk is largely attributed to long periods of absence from the family [11, 13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Long distance truck drivers and their helpers (hereafter referred to as truckers) are considered to be at high risk for sexually transmitted infections (STI) and HIV in many parts of the world, including Asia [14], Africa [58], South America [9, 10] and the United States [11, 12]. Truckers’ increased HIV risk is largely attributed to long periods of absence from the family [11, 13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Long-haul truck drivers and their commercial sex contacts (CCs; women and men with whom they exchange money and/or drugs for sex) have been implicated in the spread of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) along major transportation routes in developing countries. [1][2][3][4][5][6][7][8][9][10][11] Results from studies of long-haul truck drivers suggest that they have low HIV/STI knowledge, 12 have higher reported rates of STIs, 5,[12][13][14][15][16][17][18][19] engage in sex with multiple regular and commercial partners while on the road, 5,9,18,[20][21][22][23][24][25][26] report low condom use, 12,16,22,23 and engage in illicit drug use. 23 There is a paucity of literature on the HIV/STI risk behaviors of the approximately 800,000 to 1.2 million long-haul truck drivers 27 and their CCs in the United States.…”
mentioning
confidence: 99%
“…Another study in Bolivia on truck drivers reported that 31 % of them never used condoms while 43 % used them within the last month. The latter percentages are somewhat worse than ours but truck drivers are known to be particularly at risk by travelling across large areas all year long [ 13 ].…”
Section: Discussionmentioning
confidence: 67%